2010
DOI: 10.1111/j.1472-8206.2009.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the treatment of chronic ischemic heart disease: prognostic implications

Abstract: Stable angina is a common presentation of coronary artery disease (CAD), a condition that has an important effect on patients' quality of life and survival. Although women are affected by CAD to a significant extent, the vast majority of observational and epidemiological studies, randomized trials, and clinical guidelines, have for many years focused mainly on males. In the past few years, however, as a result of studies assessing healthcare provision in men vs. women, the focus has gradually shifted to includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…6,39 It remains possible that while women with CAD tend to have less severe coronary obstructive disease than men 31 —and therefore possibly a better outcome—this may be balanced by the more severe outcomes of non-obstructive CAD among women. 43 The known gender bias in diagnosis and access to diagnostic interventions, as found in CLARIFY and elsewhere, 9,14,44,45 is likely to modify long-term prognosis. Although the present study did not explore appropriateness for interventions, there are no data to support reduced efficacy of optimal medical therapy or revascularization in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,39 It remains possible that while women with CAD tend to have less severe coronary obstructive disease than men 31 —and therefore possibly a better outcome—this may be balanced by the more severe outcomes of non-obstructive CAD among women. 43 The known gender bias in diagnosis and access to diagnostic interventions, as found in CLARIFY and elsewhere, 9,14,44,45 is likely to modify long-term prognosis. Although the present study did not explore appropriateness for interventions, there are no data to support reduced efficacy of optimal medical therapy or revascularization in women.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study did not explore appropriateness for interventions, there are no data to support reduced efficacy of optimal medical therapy or revascularization in women. 45 …”
Section: Discussionmentioning
confidence: 99%
“…They pointed out that despite the relatively high prevalence of coronary artery disease in women, there were little data on the investigation and treatment of ischaemic heart disease in this population. 45 Besides, we found that the proportions increased and the rankings rose with age for both men and women for ischaemic heart disease, cerebrovascular sequelae and other diseases, whereas the proportion decreased and the ranking dropped with age for acute upper respiratory infection. The prevalence of upper respiratory infection decreased with age in the study conducted by Zhang and Shi from 2008 to 2012.…”
Section: Discussionmentioning
confidence: 67%
“…Women with chronic stable angina are also less likely to receive treatments such as aspirin, statins and ACE inhibitors, even if recommended in current guidelines [74]. The disparity in investigation and treatment can, in part, be attributed to the sex differences in clinical presentation and distribution of disease [75,76]. Women have a higher prevalence of angina but symptomatic women undergoing coronary angiography have less extensive and severe obstructive CAD.…”
Section: Percutaneous Coronary Intervention Versus Coronary Artery Bymentioning
confidence: 96%